OCCUPATIONAL RADIATION EXPOSURE OF THE EYE IN NEUROVASCULAR INTERVENTIONAL PHYSICIAN - Kato, Mamoru; Chida, Koichi; Ishida, Takato; Toyoshima, Hideto; Yoshida, Yasuyuki; Yoshioka, Shotaro; Moroi, Junta; Kinoshita, Toshibumi (Radiation protection dosimetry, 2019)
Neurovascular interventional radiology (neuro-IR) procedures tend to require an extended fluoroscopic exposure time and repeated digital subtraction angiography. To evaluate the actual measurement of eye lens dose using a direct eye dosemeter in neuro-IR physicians is important. Direct dosimetry using the DOSIRIS™ (IRSN, France) [3 mm dose equivalent, Hp(3)] was performed on 86 cases. Additionally, a neck personal dosemeter (glass badge) [0.07 mm dose equivalent, Hp(0.07)] was worn outside the protective apron to the left of the neck. The average doses per case of neuro-IR physicians were 0.04 mSv/case and 0.02 mSv/case, outside and inside the radiation protection glasses, respectively. The protective effect of radiation protection glasses was approximately 60%. The physician eye lens dose tended to be overestimated by the neck glass badge measurements. A correct evaluation of the lens dose [Hp(3)] using an eye dosemeter such as DOSIRIS™ is needed for neuro-IR physicians.